2020
DOI: 10.1080/10408444.2020.1854678
|View full text |Cite
|
Sign up to set email alerts
|

Using mechanistic information to support evidence integration and synthesis: a case study with inhaled formaldehyde and leukemia

Abstract: Formaldehyde is one of the most comprehensively studied chemicals, with over 30 years of research focused on understanding the development of cancer following inhalation. The causal conclusions regarding the potential for leukemia are largely based on the epidemiological literature, with little consideration of cancer bioassays, dosimetry studies, and mechanistic research, which challenge the biological plausibility of the disease. Recent reanalyzes of the epidemiological literature have also raised significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…Formaldehyde enters the body mainly during breathing and it is absorbed in the upper and lower respiratory tract, where it is rapidly metabolized, thanks to which its concentration in the blood is relatively constant [ 34 , 39 , 45 , 58 ]. A small amount of formaldehyde penetrates the body through the skin and is ingested with food and drink [ 41 , 59 ].…”
Section: Electrochemical Sensors For the Detection Of Chemical Carcin...mentioning
confidence: 99%
See 2 more Smart Citations
“…Formaldehyde enters the body mainly during breathing and it is absorbed in the upper and lower respiratory tract, where it is rapidly metabolized, thanks to which its concentration in the blood is relatively constant [ 34 , 39 , 45 , 58 ]. A small amount of formaldehyde penetrates the body through the skin and is ingested with food and drink [ 41 , 59 ].…”
Section: Electrochemical Sensors For the Detection Of Chemical Carcin...mentioning
confidence: 99%
“…One study showed that exposure to formaldehyde increases the risk of chromosomal aberrations occurring in the course of AML (chromosome 7 monosomy and chromosome 8 trisomy); however, the methodology of the study is now questioned and the need to repeat it is indicated [ 62 , 63 , 64 , 65 , 66 ]. The IARC classified formaldehyde as a human carcinogen (group 1), capable of inducing nasopharyngeal cancer (2004) and leukemia (2012), especially AML [ 8 , 39 , 45 , 47 , 58 ]. Despite the toxic effect of formaldehyde on cells, the mechanism by which it can induce leukemia is unclear [ 39 , 58 ].…”
Section: Electrochemical Sensors For the Detection Of Chemical Carcin...mentioning
confidence: 99%
See 1 more Smart Citation
“…56,58,144−147 It remains highly debatable whether FA causes nasopharyngeal cancer and leukemia in humans. 148,149 FA is a highly reactive chemical, and its DNA-damaging ability is well documented. 49,55,57,58,79,92,145,146 FA can directly target DNA to form diverse DNA lesions, including DNA monoadducts, DNA−DNA cross-links and DNA−protein cross-links (DPC), as illustrated in Figure 3.…”
Section: Case Studies Of Quantifying Dna Adducts With Silmsmentioning
confidence: 99%
“…FA, one of the top 20 highest volume production industrial chemicals, induces nasal tumors in rats at high doses (6 ppm and above) and has been classified as a Group 1 Human Carcinogen by International Agency for Research on Cancer (IARC), whereas European Chemical Agency (ECHA) classifies FA as a Group 1b carcinogen, solely based on its potential to cause nasal tumors. ,,− It remains highly debatable whether FA causes nasopharyngeal cancer and leukemia in humans. , FA is a highly reactive chemical, and its DNA-damaging ability is well documented. ,,,,,,, FA can directly target DNA to form diverse DNA lesions, including DNA monoadducts, DNA–DNA cross-links and DNA–protein cross-links (DPC), as illustrated in Figure .…”
Section: Case Studies Of Quantifying Dna Adducts With Silmsmentioning
confidence: 99%